Belgischgezinde Limburgers in de jaren 1918-1919: landverraders! (Publications de la Société Historique et Archéologique dans le Limbourg, 2024)
Belgian-minded Limburgers in the years 1918-1919: traitors! Already during the First World War the Belgian government developed plans to annex parts of the Netherlands after the war, such as the province of Limburg. Some sources claim that several Limburgers were received by American and French top officials in Paris and Brussels to talk about a referendum on the matter in Limburg. This however is doubtful. In the media and on the street people who were suspected of supporting the Belgian goals rapidly were branded as annexionists and even as traitors. The most eye-catching in Limburg were Henri van Groenendael, member of the House of Representatives of The Netherlands, Ferdinand Hustinx, editor of the magazine De Kronijk in the town of Valkenburg, the brewer Nicolaas Gilissen from Sint Pieter and the Maastricht wine merchant Hyacinthe de Beaumont. Why were they so criticized? Four apparently unrelated stories that contribute to the picture of a period in which it was up to the Dutch government to parry Belgian demands at the Peace Conference in Paris in 1919. Bottom line you might argue that the Dutch government even benefited from the fact that there were a few countrymen who gave an extra impulse to the already fierce reactions from anti-annexionists to these demands. Moreover, this underlined that a possible referendum on the matter in Limburg would be futile from the start.